The Efficacy of Cardiac Myosin Inhibitors Versus Placebo in Patients with Symptomatic Hypertrophic Cardiomyopathy - Yassen, Mohammand (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.